Effect of flake graphite content on wear between behavior between P/M copper-based pantograph slide and contact wire. (15th July 2020) - Huang, Jianxiang; Wang, Man; Li, Yaochuan; Xu, Enze; Jiang, Ke; Li, Meng; Zhong, Honghai; Liu, Junwu; Jiang, Yang
Abstract: In this work, chromium-containing copper matrix com0posites with different flake graphite content (1.8 wt%, 2 wt%, 2.5 wt%) were fabricated by inexpensive powder metallurgy method, and the mechanical properties, friction properties and microstructure of graphite/copper matrix composites were studied. Friction experiments were conducted with copper-based composite materials and copper rings to examine the effect of graphite on the wear of the bow-net structure. During mechanical wear, the wear rate of the copper ring corresponding to the sample increased with the increase of the graphite content in the sample, while the wear rate of the copper ring corresponding to the 1.8 wt% sample was the smallest. In the current-carrying wear process, the wear rate of the 2 wt% sample corresponding to the copper ring is the lowest. Through elemental analysis, it was found that material transfer occurred on the worn surface during wear. In the process of mechanical wear without current-carrying wear is caused primarily by adhesion, abrasion, and oxidation. In the process of current-carrying wear, wear is mainly caused by adhesion, electrical, and oxidative abrasion.